The effect of low dose teophillyne on the improvement of copd assessment test score, interleukin-8 level and sputum neutrophil count in patients with stable COPD - Yusup Subagio Sutanto; Magdalena - Sutanto; Hendra - Kurniawan (Universitas Syiah Kuala, 2019)
Background: Harmful particles from cigarette smoke induces an inflammatory immune response in the lungs, followed by the release of proinflammatory cytokines such as TNF-α and IL-8 and damages histone deacetylase 2 (HDAC2) in the cell core leading to glucocorticoid resistance in COPD. Low dose Theophylline of below 10mg/L has an anti-inflammatory effect by activating HDAC. This study aimed to analyze the effect of low dose theophylline on the clinical improvement of stable COPD patients assessed by the COPD Assessment Test (CAT) score, IL-8 level, and sputum neutrophil count.Methods: We conducted a quasi-experimental clinical study using a pre-post test in stable COPD patients visiting the Pulmonary Outpatient Clinic of DR. Moewardi hospital Surakarta, between July and September 2016. The samples were taken using a consecutive sampling technique, assigned into two groups, treatment, receiving standard therapy plus 70 mg low dose theophylline per 8 hours, and control receiving standard therapy only. CAT score, IL-8 level, and sputum neutrophil count were measured at baseline and four weeks after treatment.Results: The treatment group's CAT score decreased by 3.67±3.58 pg/ml and increased by 2.40±3.38 pg/ml in the control group (p=0.003). IL-8 level decreased by 4.31±13.06 pg/ml in the treatment group and increased by 0.88±13.89 pg/ml in the control group (p=0.116). The sputum neutrophil count decreased in both treatment and control groups by 4.00 ±40.33 pg/ml and 2. 87±39. 91 pg/ml (p=0.939).Conclusion: Statistically low dose theophylline significantly lowers the CAT score of stable COPD patients. It also decreases IL-8 level and sputum neutrophil count, although it is not significant.